2019
DOI: 10.1111/1365-2745.13193
|View full text |Cite
|
Sign up to set email alerts
|

Microbial “gardening” by a seaweed holobiont: Surface metabolites attract protective and deter pathogenic epibacterial settlement

Abstract: Epimicrobial communities on seaweed surfaces usually contain not only potentially pathogenic but also potentially beneficial micro‐organisms. Capacity of terrestrial plants for chemically mediated recruitment, that is, “gardening” of bacterial communities in the rhizosphere was recently demonstrated. Empirical evidence directly linking such chemical “gardening” with the beneficial role of gardened microbes in terrestrial plants is rare and largely missing for aquatic macrophytes. Here, we demonstrate that our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 64 publications
(106 reference statements)
4
106
0
Order By: Relevance
“…Seaweed metabolites are known to affect bacterial attachment and growth (reviewed by Saha et al, 2017). Also, it has been demonstrated that seaweed surface metabolites can influence the overall epibacterial community composition when compared to non-living substrata (Lachnit et al, 2010) and can selectively attract beneficial and repel pathogenic bacteria (Saha and Weinberger, 2019). Thus, only microorganisms which can adapt to the specific surface chemistry conditions on a host surface might be able to settle on it, fitting the 'niche' model (Dumbrell et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seaweed metabolites are known to affect bacterial attachment and growth (reviewed by Saha et al, 2017). Also, it has been demonstrated that seaweed surface metabolites can influence the overall epibacterial community composition when compared to non-living substrata (Lachnit et al, 2010) and can selectively attract beneficial and repel pathogenic bacteria (Saha and Weinberger, 2019). Thus, only microorganisms which can adapt to the specific surface chemistry conditions on a host surface might be able to settle on it, fitting the 'niche' model (Dumbrell et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To cope with seasonally fluctuating colonizing pressure, macrophytes including seaweeds in turn have been reported to seasonally up or downregulate the production of antifouling defense (Saha and Wahl, 2013;Wang et al, 2017;Guan et al, 2019) influencing seaweed-bacteria interaction and also interaction with other foulers. We have recently demonstrated that the surface chemistry of Agarophyton is capable of selectively recruiting bacterial colonizers (Saha and Weinberger, 2019) and from previous studies we are aware that the antifouling defense of seaweeds including Agarophyton undergoes seasonal fluctuations indicating a change in the surface chemistry of the alga over time (Saha and Wahl, 2013;Wang et al, 2018). Although in this current study we have not investigated the surface metabolome of Agarophyton at different timepoints, i.e., T0, T1, and T2, we may speculate that a seasonal fluctuation in the surface chemistry of the algae may have resulted in the selective recruitment of the bacterial colonizers on the surface of the alga and thereby different community composition at different timepoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial gardening -the act of frequently releasing growth-enhancing or inhibiting chemicals or metabolites that favor the development of a microbial community beneficial to the host (see e.g. Saha and Weinberger 2019). Microbiome -the combined genetic information encoded by the microbiota; may also refer to the microbiota itself or the microbiota and its environment (see Marchesi and Ravel 2015).…”
Section: Glossarymentioning
confidence: 99%
“…Alternatively, colonization might occur in a neutral manner, comparable to other Alteromonas spp. with a similar CAZyme profile 80 . Considering nucleotide substitution rates of ca.…”
Section: Resultsmentioning
confidence: 94%